2010
DOI: 10.1002/cjoc.201090103
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction on a Rotating Ag/GC Disk Electrode in Acidic Solution

Abstract: Finding an appropriate mechanism of oxygen reduction reaction, without having kinetic parameters and intermediate species at hand, is an impossible task. In view of the fact that this reaction is one of the important reactions, it was tried to overcome this problem through computing the kinetic parameters by means of Ag/GC rotating disc electrode in an acidic solution. Using this electrode, two values were obtained for electron transfer coefficient and reaction order was calculated through relative equations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Oxygen reduction reaction (ORR) has gained a standing interest in the last 20 years as a result of the wide range of applications that it is involved in, such as chemical and biochemical analysis, pharmaceutics, corrosion, energy conversion, and fuel cells [1]. It has been, for a long time, one of the most studied redox processes, both from mechanistic [2,3] and kinetic [4][5][6] aspects. Indeed, several different mechanisms may be invoked to account for O 2 reduction, the most commonly reported being either a four-electron Bdirect^pathway (Reaction 1) [7] The main parameters that impact on mechanistic pathway are the operating media and electrode materials [8], and some authors have reported more complex reduction paths on alloys and noble metals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen reduction reaction (ORR) has gained a standing interest in the last 20 years as a result of the wide range of applications that it is involved in, such as chemical and biochemical analysis, pharmaceutics, corrosion, energy conversion, and fuel cells [1]. It has been, for a long time, one of the most studied redox processes, both from mechanistic [2,3] and kinetic [4][5][6] aspects. Indeed, several different mechanisms may be invoked to account for O 2 reduction, the most commonly reported being either a four-electron Bdirect^pathway (Reaction 1) [7] The main parameters that impact on mechanistic pathway are the operating media and electrode materials [8], and some authors have reported more complex reduction paths on alloys and noble metals [11].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen (O 2 ) reduction reaction (ORR) is probably one of the most studied redox processes in the literature, both from the mechanistic [1][2][3] and kinetic [4][5][6][7][8] points of view. Amongst the numerous works dealing with this electrochemical system, the Damjanovic model is of particular interest which describes the ORR as a multi-electron reaction [9].…”
Section: Introductionmentioning
confidence: 99%